2016
DOI: 10.1177/0271121416672185
|View full text |Cite
|
Sign up to set email alerts
|

An Examination of the Quality of Discipline Policies in NAEYC-Accredited Early Care and Education Programs

Abstract: It is estimated that between 10% and 21% of preschool children exhibit challenging behavior (Snell et al., 2012). Children identified as having aggressive behavior in preschool are more likely to experience continuing behavior problems throughout elementary school and into adoles

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 38 publications
0
13
0
3
Order By: Relevance
“…These centre‐wide rules are often written into policy, and only 63 per cent of our participants selected ‘sharing programme policies' as a way to involve parents and prevent and address challenging behaviour. In their examination of discipline policies of NAEYC centres, Garrity and others () found that approximately 7 per cent of programme policies contained behavioural expectations with clarity and had consistent programme‐wide behavioural expectations. Taken together, these data suggest a need for increased professional development related to the efficacy and implementation of school‐wide PBS in early childhood and the role of high‐quality policies in supporting implementation of the Pyramid Model.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These centre‐wide rules are often written into policy, and only 63 per cent of our participants selected ‘sharing programme policies' as a way to involve parents and prevent and address challenging behaviour. In their examination of discipline policies of NAEYC centres, Garrity and others () found that approximately 7 per cent of programme policies contained behavioural expectations with clarity and had consistent programme‐wide behavioural expectations. Taken together, these data suggest a need for increased professional development related to the efficacy and implementation of school‐wide PBS in early childhood and the role of high‐quality policies in supporting implementation of the Pyramid Model.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Snell and others () reported that only 14 per cent of survey respondents described using strategies from a social‐emotional curriculum, often an important part of tier two strategies, to prevent challenging behaviours. Finally, Garrity and others () reported that only 14 per cent of programmes had policies that specifically addressed the need for intentional, small‐group teaching strategies targeting social‐emotional development. Given these findings, it may be beneficial for professional development efforts in the United States to target the importance of second tier strategies and provide practical, hands on examples of what these strategies look like in the early childhood classroom.…”
Section: Discussionmentioning
confidence: 99%
“…Developmentally appropriate, high-quality discipline policies that support positive social behavior and reduce challenging behavior in young children are a necessary and an effective component of service delivery systems (Garrity et al, 2017; U.S. Department of Education Office for Civil Rights, 2014b). Longstreth et al (2013) examined the quality of discipline policies in state-licensed early childhood programs in in Arizona.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The U.S. Department of Health and Human Services (2014) also issued a joint policy statement calling for the elimination of suspension and expulsion in early learning settings and emphasizing the importance of teaching positive social behavior skills. Despite these national efforts calling for high-quality, developmentally appropriate discipline policies, researchers found that early childcare systems lack high-quality discipline policies to reduce and prevent challenging behavior (Garrity et al, 2017;Longstreth et al, 2013).…”
Section: Developmentally Appropriate Discipline Policiesmentioning
confidence: 99%
See 1 more Smart Citation